PROFIL VERTIKAL KANDUNGAN OKSIGEN TERLARUT DAN FLUORESENCE IN VIVO SEBAGAI INDIKATOR KEBERLANGSUNGAN KEHIDUPAN DI PERAIRAN LAUT MALUKU DAN LAUT SULAWESI - iis triyulianti; Indra Hermawan; Agung Yunanto; Novia Arinda Pradisty; Aditya Chandra Raymonza; Fikrul Islamy; Nadia Christa Magdalena (Pusat Riset Kelautan, 2017)
Indeso Joint Expeditions Cruise (IJEP) activity in 2016 measured some water quality parameters, one of them are dissolved oxygen and in vivo fluorescence for expressing biomass of phytoplankton community.Those parameters were measured for analyzing the important component of marine biogeochemical cycle used the titrimetric method and optical sensor. Expedition of IJEP was conducted on September 5-15, 2016 from the port of P2LD-LIPI Ambon into Bitung port, North Sulawesi. Measurement results of Dissolved Oxygen (DO) at 21 stations showed varied values vertically and horizontally. Vertical distribution of DO and fluorescence were measured at seven of depth water (10, 50, 60-150, 300, 500, 750 dan 1000 meter). Distribution of DO decreased through ocean inventory with its range values was 3,334 – 7,321 mg/L. Depletion of dissolved oxygen from surface layer into the upper of thermocline layers (50 – 400 meter). The concentration of DO decreased after chlorophyll maximum layer (represent as in vivo fluorescence) at different of depth water with its range value was 0,4441 – 1,1376 mg/m3. The concentrations of dissolved oxygen were higher both vertically and horizontally in Sulawesi Sea than in Maluku Sea at this transitional season (September 2016) but inversely condition for the in vivo fluorescence in which it’s higher in Maluku Sea. There was an indication of internal upper water mass impacts on the highest concentration of in vivo fluorescence in Maluku Sea. These results indicate that Maluku Sea and Sulawesi Sea have the carrying capacity of the ecosystem for sustainability of their marine life.